The secrets of college success - Jacobs, Lynn F., 1955-; Hyman, Jeremy S. (Professor's guide., 2013)
This guide combines easy-to-follow tips with insider information from professors themselves. Topics include advice on picking courses and choosing a major, time management and study skills, staying on top of core requirements, getting good grades, interacting effectively with professors, and avoiding stress.